PENGARUH NILAI PELANGGAN TERHADAP RETENSI PELANGGAN MELALUI KEPUASAN - Win Esti; Nawazirul Lubis; Andi Wijayanto (Universitas Diponegoro, 2014)
This study aimed to determine the effect of customer value on customer retention through customer satisfaction who use Smartfren data services on student majoring in Business Administration, University of Diponegoro class of 2009 to 2012. This type of research is explanatory research, by using a survey method of data collection tools such as questionnaires. The number of respondents were 63 persons obtained by sensus. Tests using the research instrument validity and reliability test, whereas data analysis techniques used simple linear regression, t-test, and path analysis with SPSS 16.0 tools. These results indicate that the effect given by the variable customer value (X1) and satisfaction variables (Y1) to variable customer retention (Y2) respectively - amounted to 26.2 % and 23.6 %. Results of simple linear regression between variables showed a positive regression coefficient, this means the higher the customer value and satisfaction, it will also result in higher customer retention. Advice can be given that the company needs to maintain customer satisfaction through increased customer value with continuous improvement efforts on the quality of data service connectivity, expansion of network coverage, improved service standards either directly or indirectly (via SMS, call center, or the official site). This effort is done so that consumers feel satisfied, and proud of the product, especially Smartfren data services, so that consumers do not switch to another data service provider, and is willing to give a positive recommendation.